PROSPECTS FOR THE DEVELOPMENT OF HYDROGEN ENERGY IN THE CONTEXT OF THE GLOBAL ENERGY TRANSITION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article analyzes current trends in the development of hydrogen energy within the framework of the global energy transition and international policy. Key factors driving the adoption of hydrogen technologies are examined, including the need to reduce greenhouse gas emissions, ensure energy security, and achieve sustainable development goals. The research methodology is based on a systematic analysis of scientific and statistical data, as well as a review of political strategies adopted by various countries for the implementation of renewable energy sources. Particular attention is given to international cooperation, the economic and environmental benefits of hydrogen energy, as well as the challenges associated with the use of rare earth elements and infrastructure development. The research findings confirm the necessity of a comprehensive approach to building a sustainable energy system that incorporates innovative technologies, international coordination, and effective resource management.
Keywords: hydrogen energy, renewable energy sources, sustainable development, international cooperation, environmental policy